Pretoria Student Law Review 2018-12 (Pretoria University Law Press (PULP), 2018)
It is with great joy that I, along with the editorial committee, present to you the reader, the 2018 Pretoria Student Law Review. In the past twelve years, the journal has gone from strength to strength and nowhere is this more evident than in this year's edition. We have received more submissions and published more articles than previous years. We have expanded the reach of the journal by including authors from not only outside UP but also outside the borders of South Africa. Fittingly, the wide range of articles in this year's edition are topical, engaging and critical of the law. Most importantly, the articles spark conversation. If this is the quality of writing that Africa as a continent can produce, we as law students, young scholars and future legal practitioners can only reach new heights. I am proud of the work that the authors have put into their articles, but especially I am proud of the editorial committee and the work they have done to ensure that the PSLR delivers quality articles. The role of an editor is difficult, time consuming and often thankless and therefore I would like to thank the 2018 editorial committee - Primrose E.R. Kurasha, Agnes Matasane, Vaughn Rajah and Kirstin Swanepoel. Without your hard work and dedication to this journal, nothing would have been possible, it has been a privilege to work with all of you. Furthermore, I would like to thank Prof Karin van Marle for her guiding hand that shepherded us throughout the highs and lows of this year. To Lizette Hermann, thank you for your dedication to the PSLR. About the cover, I would like to thank Adebayo Okeowo for his submission. The cover and back page compliment the Year of the Women as celebrated throughout the year by the Law Faculty and UP Law House in particular. Turning to the future, it is with pride that I can say that I leave the PSLR in the custody of strong hands and even sharper minds. To you future author, I implore you to continue writing. To you the reader I say expand your mind, question all that is in front of you - for this is the only way we, as scholars, grow. Jurgen Zwecker Managing editor 2018